Designing Synergistic Biostimulants Formulation Containing Autochthonous Phosphate-Solubilizing Bacteria for Sustainable Wheat Production - Yahya, Mahreen; Rasul, Maria; Sarwar, Yasra; Suleman, Muhammad; Tariq, Mohsin; Hussain, Syed Zajif; Sajid, Zahid Iqbal; Imran, Asma; Amin, Imran; Reitz, Thomas; Tarkka, Mika Tapio; Yasmin, Sumera (Frontiers in Microbiology, 2022)
Applying phosphate solubilizing bacteria (PSB) as bio-fertilizers has enormous potential for sustainable agriculture. Despite this, there is still a lack of information regarding the expression of key genes related to phosphate-solubilization (PS) and efficient formulation strategies. In this study, we investigated rock phosphate solubilization by Ochrobactrum sp. SSR (DSM 109610) by relating it to bacterial gene expression and searching for an efficient formulation. qPCR primers were designed for PS marker genes glucose dehydrogenase (gcd), pyrroloquinoline quinone biosynthesis protein C (pqqC) and phosphatase (pho). SSR inoculated soil supplemented with rock phosphate (RP) showed a 6-fold higher expression of pqqC and pho compared to inoculated soil without RP. Additionally, an increase in plant P (2%), available soil P (4.7%) and alkaline phosphatase (6%) activity was observed in PSB-inoculated plants supplemented with RP. Root architecture improved by SSR, with higher root length, diameter and volume. Ochrobactrum sp. SSR was further used to design bioformulations with two well characterized PS, Enterobacter spp. DSM 109592 and DSM 109593, using four organic amendments, biochar, compost, filter mud and humic acid. All four carrier materials maintained adequate survival and inoculum shelf life of the bacterium, as indicated by field emission scanning electron microscopy analysis. Filter mud (FM) based bio-formulation was most efficacious and enhanced not only wheat grain yield (4-9%) but also seed P (9%). Moreover, FM based bio-formulation enhanced soil available P (8.5-11%) and phosphatase activity (4-5%). Positive correlations were observed between the PSB solubilization in presence of different insoluble P sources, and soil available P, soil phosphatase activity, seed P content and grain yield of field grown inoculated wheat variety Faisalabad-2008, when di-ammonium phosphate fertilizer application was reduced by 20 %. The present study reports for the first time marker gene expression of an inoculated PSB strain and provides a valuable groundwork to design field scale formulations that can maintain inoculum dynamics and increase its shelf life. This may constitute a step-change in the sustainable cultivation of wheat under P-deficient soil conditions.